If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(X + X + -7) = 3(X + 9 + X + 2 + X + -7) Reorder the terms: 2(-7 + X + X) = 3(X + 9 + X + 2 + X + -7) Combine like terms: X + X = 2X 2(-7 + 2X) = 3(X + 9 + X + 2 + X + -7) (-7 * 2 + 2X * 2) = 3(X + 9 + X + 2 + X + -7) (-14 + 4X) = 3(X + 9 + X + 2 + X + -7) Reorder the terms: -14 + 4X = 3(9 + 2 + -7 + X + X + X) Combine like terms: 9 + 2 = 11 -14 + 4X = 3(11 + -7 + X + X + X) Combine like terms: 11 + -7 = 4 -14 + 4X = 3(4 + X + X + X) Combine like terms: X + X = 2X -14 + 4X = 3(4 + 2X + X) Combine like terms: 2X + X = 3X -14 + 4X = 3(4 + 3X) -14 + 4X = (4 * 3 + 3X * 3) -14 + 4X = (12 + 9X) Solving -14 + 4X = 12 + 9X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9X' to each side of the equation. -14 + 4X + -9X = 12 + 9X + -9X Combine like terms: 4X + -9X = -5X -14 + -5X = 12 + 9X + -9X Combine like terms: 9X + -9X = 0 -14 + -5X = 12 + 0 -14 + -5X = 12 Add '14' to each side of the equation. -14 + 14 + -5X = 12 + 14 Combine like terms: -14 + 14 = 0 0 + -5X = 12 + 14 -5X = 12 + 14 Combine like terms: 12 + 14 = 26 -5X = 26 Divide each side by '-5'. X = -5.2 Simplifying X = -5.2
| 5x+8x-20=0 | | -2+0.9+0.5(-2)=-2.1 | | (X)(-x)(-2x)= | | 3X^2-XY=0 | | (X)(2x)(y)= | | (5x)(2x)(x)= | | 6-2x=2(1x+3) | | X=5s | | 2(7-x)+5(x+1)=10(1+x)-9(x+1) | | 400=49.91x | | 9(2x+3)=18x+27 | | 5.70=0.05x+1.70 | | 14x+43-25x=229 | | y=0.05(27)+1.70 | | 5x+8x+3x-4y= | | .25x+.5(71-x)=22 | | 8-4x=2(2x+4) | | 94-4p-6p=-1 | | 5x=100y | | 2x+(x-56)=3x | | 9r-28=-3+4r | | X-9=4x+6 | | 7r-11=-23+9t | | -2x^2+13=-43 | | 3x+3=7+7x | | 7d+40=10 | | 4x+2x+3=6x | | W^2+13w=608 | | 7x+2=9x-2x+2 | | (7x+7)+(4x+52)=180 | | 6m(15m+6)=78 | | 32=-2+7b |